Prohibition of RIBA : the implimentation of Ta’widh And Gharamah in Islamic financial system / Nur Aqilah Shahrizal - Shahrizal, Nur Aqilah (2019)
The knowledge of implementation of riba ta’widh and gharamah is very importance among the societies in Malaysia. This is because, nowadays, some people especially Muslims do not aware with transaction that related to riba and they also do not understand properly and deeply about the implementation of ta’widh and gharamah in Islamic Banking in Malaysia. They think that the implementation of ta’widh and gharamah is not difference with usury in conventional bank. As we know, riba is prohibited in Islam which is doing any transaction that related to riba is prohibited. Then, there also have many issues contemporary that related to riba and also the issues that like a riba transaction but actually there are not riba transactions. Therefore, this study focuses on investigate about the implementation of riba in conventional bank and the issues implement in daily life and also investigate the concept and implementation of ta’widh and gharamah is allowed by Islam or not.